Differential effects of Huang-Lian-Jie-Du Decoction on Alzheimer’s disease and normal rats - Xu, Manru; Zhu, Yue; Chen, Jinxin; Zhong, Furong; Wang, Ruoli; Li, Jie; Qiao, Mengyuan; Fan, Yiran; Ren, Pan; Chen, Mingqi; Qin, Jingbo; Wu, Wenbin (Frontiers in Pharmacology, 2025)
IntroductionHuang-Lian-Jie-Du Decoction (HLJDD), a botanical drug used in traditional medicine, has been used in the management of Alzheimer’s disease (AD). However, the mechanisms underlying its preventive effects remain inadequately understood, particularly due to the absence of metabolomic studies examining alterations in serum and cerebrospinal fluid (CSF) metabolites. Moreover, the potential toxicities and side effects of HLJDD necessitate further pharmacological investigation. This study aims to explore the differential effects of HLJDD on AD model rats and healthy controls through a metabolomics approach and uncover the underlying mechanisms based on changes in serum and CSF metabolites. The findings are expected to provide a scientific foundation for enhancing the clinical safety and rational use of HLJDD.MethodsThe composition of HLJDD was characterized by UPLC-Q-Exactive Orbitrap HRMS. Aβ1-42-induced SD rats served as the AD animal model. Rats in the sham + HLJDD and Aβ1-42 + HLJDD groups (0.604 g/kg freeze-dried powder) were treated with HLJDD via gavage for 28 days. Nissl staining was performed to assess hippocampal neuronal changes, while H&E staining was used to evaluate histopathological alterations in the brain, liver, kidneys, stomach, large intestine, and small intestine. Aβ expression was determined using IHC and ELISA, and inflammatory levels in both peripheral and central systems were quantified by ELISA. MMP-2 and MMP-9 expression were analyzed through IHC. LC-MS was employed to investigate metabolic variations in serum and CSF.ResultsHLJDD reduced Aβ deposition in Alzheimer’s disease rats, enhanced neuronal survival, reduced inflammation, preserved blood-brain barrier (BBB) integrity, and alleviated damage to the brain, kidneys, and stomach. These therapeutic effects were associated with the arginine biosynthesis pathway and ferroptosis. In contrast, HLJDD induced peripheral and central inflammation, impaired neuronal function, compromised BBB integrity, and caused damage to the liver, kidneys, and large intestine in normal rats. These adverse effects were linked to disruptions in aminobenzoate degradation and nucleotide metabolism.ConclusionHLJDD may alleviate Aβ-induced damage repair in Alzheimer’s disease rats, but it also induces varying degrees of toxicity in normal rats.